E-117 Outcomes of endovascular treatment in direct versus transfer patients; TRANSFER study: a preliminary analysis. (22nd July 2019) - Zafar, A; Suriya, S; Farooqui, M; Owens, O; Alvarado Arias, A; Ikram, A; Sorte, D; Carlson, A; Torbey, M
Abstract : Objectives: The primary objective is to evaluate difference in outcomes after endovascular treatment (EVT) between patients directly admitted through Emergency Department (ED) and patients transferred from outside institutions. Background: Over last few years, EVT has been established as the most-effective treatment for acute ischemic stroke (AIS) patients with large vessel occlusion (LVO). In New Mexico state, University of New Mexico Hospital (UNMH) serves as the only institution providing 24/7 services for EVT. In addition to transfers, patients are also admitted directly to UNMH through ED to undergo EVT. Considering the dynamics of New Mexico sate, representing various other similar states, we are conducting this study to evaluate any significant difference in the outcome of transferred patients in comparison to directly admitted patients. Methods: This is an observational retrospective cohort study. Patients who underwent EVT for LVO from January 01, 2018 to December 31, 2018 at UNMH were included. Data was collected on secured Redcap™ database. Patients were categorized into direct admission (DA) vs transfer groups (TG). Patients who were not candidates for EVT were excluded. Results: A total of 53 patients underwent EVT. Seventeen patients were directly admitted through ED while 36 were transferred from outside hospitals. Age, gender, ethnicity and risk factor profile are reported in table 1. The two groups had similar NIHSS and GCS on presentation. The median time of arrival of patients to UNM, from last known well, was 211 minutes in DA and 321 minutes in TG (p=0.03). Median UNM arrival to groin puncture time was 121 minutes in DA and 66 minutes in TG (p=0.04). Median procedural time for recanalization was 41 minutes for DA and 28 minutes for TG. One patient had unsuccessful thrombectomy (TICI score of 0). Although no statistical significance was noted, mean mRS at 3 months was 3 in each group. The 3-month mortality was similar in the two groups (DA=23.5% vs TG=25%). Conclusion: To the best of our knowledge, this is the first study reporting EVT data reflecting experiences from an academic program of an underserved state after the expansion of EVT time-window. This study showed no statistical difference in the outcomes of patients admitted directly through ED versus patients who were transferred from outside hospitals for EVT. Larger scale studies are needed to corroborate this data. Disclosures: A. Zafar: None. S. Suriya: None. M. Farooqui: None. O. Owens: None. A. Alvarado Arias: None. A. Ikram: None. D. Sorte: None. A. Carlson: None. M. Torbey: None.